A case report of severe hypertriglyceridemia induced acute pancreatitis managed with continuous insulin infusion - Thomas, Joseph (International Journal of Research in Medical Sciences, 2024)
31-year-old male, chronic alcoholic presented to the emergency room with epigastric pain, nausea and vomiting. On examination he was febrile, had abdominal distention with tenderness in the epigastric region. His lipase was elevated and computed tomography of abdomen showed evidence of acute pancreatitis. His past history was significant for chronic myeloid leukemia on imatinib and poorly controlled type 2 diabetes mellitus. Laboratory studies revealed elevated triglyceride levels (5254 mg/dl) and uncontrolled blood sugars (HbA1c-10.77%). Due to the severity of his pancreatitis presentation, he was admitted to the intensive care unit. He received aggressive intravenous fluid hydration and was started on continuous insulin infusion. He improved significantly with insulin therapy. His triglyceride levels decreased from 5254 mg/dl to 1891 mg/dl after 48 hours of initiating insulin therapy, by fifth day of admission triglycerides were below 500 mg/dl and was clinically better. He was discharged with a basal dose of insulin and fenofibrates. Intravenous insulin infusion is an effective, affordable, and accessible therapy for acute pancreatitis due to severe hypertriglyceridemia.